PROFIT MANAGEMENT IN ISLAM AND THE FACTORS - Devi Permatasari (UNISSULA, 2018)
Profit Management is a phenomenon that is influenced by various factors. Among them are such as information asymmetry and free cash flow. In Indonesia alone there are already cases of profit management from several years ago. This study aims to determine the influence of information asymmetry, and free cash flow on profit management practices in manufacturing companies listed on the Stock Exchange. The population of this study are the manufacturing companies that listed in Indonesia Stock Exchange (IDX) 2012-2016. The sampling technique used was purposive sampling method. The method of analysis used in this study using multiple linear regression. The total number of samples for this study are 180 companies. But, there are found 45 samples as outlier should be excluded from sample observation. So,the final samples for this study are 136 companies. The results showed that the free cash flow has influence on profit management, and information asymmetry has no effect on profit management.Keywords: Profit managements, Information Asymmetry, Free cash flow.